Evaluation of the effects of piper betle supplementation as a natural antibiotic growth promoter (NAGP) on antimicrobial activity, feed acceptance and growth performance of kelah (Tor sp.) in a tank system - Mohd Yusof, Hanan; Othman, Ahmad Baihaqi; Nik Yusof, Nik Haiha; Jaapar, Muhd Zudaidy; Abdullah, Azila; Nawi, Mohd Firdaus; Roslan, Irfan Hakimi; Mansor, Nur Nazifah (ASSOCIATION FOR AGRICULTURE ENVIRONMENT AND BIOTECHNOLOGY, 2024)
The negative side-effects of the usage of synthetic antibiotic growth promoters (AGP) in feeds for animals and humans have been widely understood, although it positively promotes growth and gives better economic returns to the farmers. Thus, the present study was conducted to evaluate the potential of Piper betle extract as an herbal product as a feed additive and a natural antibiotic growth promoter (NAGP) toward kelah (Tor sp.) on antimicrobial activity, feed acceptance, and growth performance. In this study, for antimicrobial activity, several concentration levels of Piper betle extract were tested to observe the optimum dosage for bacterial inactivation of Aeromonas hydrophila obtained from the kelah specimen. Then, in evaluating the optimal palatability of Piper betle concentration for kelah, the fish were divided into seven treatment groups, one of which was used as a control and daily fed at 3% of the fish’s body weight. In the growth study, two treatment methods were used, which were once a month (S1) and fortnightly (S2) feedings of a diet treated with 100 ppm Piper betle extract, with a non-treated Piper betle extract diet serving as a control (C). All treatments were conducted in duplicate and the fish were stocked at 10 fish m-2 in 3MT tanks. Fishes were fed ad libitum, twice daily. The results showed the optimal dosage for Piper betle extract was identified at 100 ppm with a significant different (P > 0.05) in the size of the Aeromonas hydrophila bacterial inhibitory zone, with diameters of 18.7± 0.6 mm. However, there was no significant difference between feed acceptance by kelah on a Piper betle treated diet up to 100 ppm dose and a control diet with a value of 1.32 % body weight per feeding session. While at 182 days of growth study, the results show that the best growth performance of kelah according to body weight gain (BWG) was treatment S2 with 131.9 ± 9.1 %, followed by S1 and control at 104.8 ± 10.2 % and 84.2 ± 9.5 %, with a significant difference (P <0.05). Additionally, a significant better (P <0.05) specific growth rate (SGR) of S1 and S2 treatments was valued at 0.39 ± 0.10 and 0.47 ± 0.02, respectively, compared to the control treatment at 0.34 ±0.03. While the S2 treatment significantly showed the best feed conversion ratio (FCR) compared to the S1 and control treatments, with 3.57 ±0.17, 4.27 ±1.13, and 5.02 ±0.49, respectively. In overall, there was no significant difference in survival rate among all treatments in this study. Thus, the results suggest that Piper betle can be considered as a NAGP in the diet at the optimum dose of 100 ppm, with fortnightly application as the best feeding regime for kelah culture